Quorum Quenching Bacteria Bacillus velezensis DH82 on Biological Control of Vibrio parahaemolyticus for Sustainable Aquaculture of Litopenaeus vannamei - Sun, Xiaohui; Liu, Jia; Deng, Shijing; Li, Renhe; Lv, Wenhua; Zhou, Shufeng; Tang, Xu; Sun, Yun-zhang; Ke, Mingyue; Wang, Kunming (Frontiers in Marine Science, 2022)
Aquatic pathogens such as Vibrio parahaemolyticus causes bacterial infection that reduces the economic benefits of aquaculture and affects the food quality and safety to human being. Quorum quenching (QQ) has been considered as a novel strategy of microbial antagonism to inhibit pathogens and reduce the abuse of antibiotics. In this study, a QQ bacterial stain, Bacillus velezensis DH82 from deep sea in Yap trench, is in vitro investigated on the effects of DH82 and its functional products against V. parahaemolyticus, focusing on the Quorum sensing (QS) regulation and the inhibition of pathogenicity and bacterial growth, and in vivo studied in the aquaculture of Litopenaeus vannamei challenged with V. parahaemolyticus by immersion and injection challenge. The results of QS regulator transcription level demonstrated the multiple QQ enzymes in DH82 regulated the pathogenicity but could not fully control the biofilm formation; the effective antibacterial activity of extracellular peptides on microbial antagonism verified the inhibition on bacterial growth of V. parahaemolyticus. The in vivo experiment in aquaria demonstrated the effective enrichment of DH82 and inhibition of Vibrio in both aquatic system and the shrimp intestine, the dietary DH82 relieved the negative effect of Vibrio on the activity of enzyme ACP, AKP and SOD when emerging out-breaking of Vibrio, and was not harmful to host according to the LZM activity; DH82 also ameliorated the damage of intestine and muscles induced by V. parahaemolyticus infection according to the tissue imaging. Though DH82 did presented some dose-dependent adverse effects to the host, the findings revealed the effective QQ and antibacterial activity of DH82 on emerging biocontrol against V. parahaemolyticus, therefore indicating the potential application of DH82 as biological control reagent in the sustainable and green production of aquaculture.